Alternatives to meat for halting the stable to table continuum – an update. Issue 1 (1st January 2020) - Mistry, M.; George, A.; Thomas, S.
Abstract: Irrefutable evidence of the adverse effects of meat consumption on health and environment, prompts an urgent need to raise awareness about moving from animal based dietary patterns to more plant based ones. Meat alternatives and meat analogues can help achieve this objective and at the same time satisfy the nutritional needs and the sensory appeal for the discerning palates of vegans, vegetarians, and meat-lovers. Recent research and development in the food industry has created meat analogues that may come very close to meats in their nutritional and sensory appeal. This paper presents a review of the available alternatives to meat with special emphasis on meat analogues mainly comprising soy, wheat gluten and mycoproteins. The paper also highlights the main processes involved in producing these meat analogues, their nutritional values, advantages, disadvantages and recognizes the scope of popularizing meat alternatives in Bahrain.